EVALUASI PELAKSANAAN PROGRAM PEMBERANTASAN DBD (Studi Di Wilayah Puskesmas Putat Jaya Kecamatan Sawahan Kota Surabaya Tahun 2016) - Wahyu Sulistyorini Wilujeng; Winarko .; Sudjarwo . (GEMA LINGKUNGAN KESEHATAN, 2017)
ABSTRACTDengue Haemarogic Fever (DHF) is most popular disease in this society, this disease may attack all peopleand result in death in relatively short time. In 2015, number of cases in Putat Jaya local government clinic districtSawahan Surabaya City in January-September are 42. Dengue Haemorogic fever control program should be doneby all people, not only Public Health Office, clinic but also all people, because Dengue Fever can be reduced byDengue Fever eradication. Aim of this research is evaluating the implementation of dengue haemorhagic fevercontrol program in local government clinic Putat Jaya District Sawahan in 2016.This is descriptive research, data was collected by interview and document tracking. Sample is from healthworkers and the people which was taken randomly as many as 30 people and analyzed descriptively.Based on research result, eradication activities, larvicides routine inspection, periodic inspection of larva.Aedes aegypti mosquito control have been done although it has not been thoroughly, while fogging activities infocus area has already been implemented. Number of mosquito-free for the last 3 years ≤ 95%, and not inaccordance with the requirements.Suggestions for sanitarian Putat Jaya to provide, watch, supervise and nurture a cadre of locals to carry outtheir duties and responsibilities, and to society more active in conducting control of dengue haemorogic fever,because to get the expected results, activities to eradicate dengue haemorigic fever must be donesimultaneously and continously.Keywords : Evaluation Control Program and Dengue Haemorigic Fever